GRANITOIDS OF TECTONOMAGMATIC ACTIVITY AREAS: CLASSIFICATION AND GENETIC PROBLEMS - Shevchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Genetic peculiarities and classification of granitoids in tectonomagmatic activation area are considered. Simultaneous evolution of palingene-metasomatic and metamagmatic granitoids is proved. Granitoid formation is explained by the ineraction of transmantle fluids with the solid crust substrates in the first case and different depth basit and ultrabasite melts in the second one.